"Guardian of the international order"? NATO's contested identity, the discourses of Secretaries General, and the Ukraine crisis. Issue 2 (3rd April 2018) - Böller, Florian
ABSTRACT: This article examines the role of NATO Secretaries General within the transatlantic security community in the wake of the 2014 Ukraine crisis. Drawing on a social constructivist perspective, the comparative discourse analysis of Rasmussen and Stoltenberg offers important insights regarding the role of a non-governmental actor in transatlantic relations. So far, research on transatlantic relations rarely investigated the discourses of NATO Secretaries General. The analysis shows that despite increased attention toward collective defence, both Secretaries General argued for an alliance, which is engaged not only in regional but also global affairs. As Eastern European NATO allies, especially Poland and the Baltic states, embrace divisive notions of the alliance's self and perceived threats, the security community's collective identity remains contested.